PROPAGATION OF THE ORNAMENTAL TULIP TREE (LIRIODENDRON TULIPFERA) FROM SEEDS - Aktam Nurniyozov; Rasuljon Khaydaraliev (Zeta Repository, 2023)
Tulip tree (Liriodendron tulipifera) is a member of the Magnolia family and is one of the largest native trees in the eastern United States, reaching a height of 20-58 m, a trunk diameter of 3 m, and an average height of 21 to 30 m. Tulip tree seeds are 2.5-3.5 cm and have a deep dormancy, so it takes a long time to grow. To propagate liriodendron from seed, only freshly picked seeds are suitable. Seeds are sown in substrate at the end of autumn and placed in a cool dark environment. Germination rate is about 15%. Seedlings are transplanted into small pots or containers. For planting in spring, it is necessary to stratify the seeds keep the seeds in a moist environment to accelerate their germination and treat the seeds before planting. Also, in nature seeds almost always have low viability, usually only around 10%. After germination from seeds growth in the first year usually 15 cm to 40 cm. In the second year, growth accelerates.